Summary category «value», «content» and «form» in the formulation of the concept of law - Авраменко, Л. В. (Problems of legality, 2014)
This article analyzes the relationship between the «concepts nature», «content» and «form» of law. Various areas of law, reveal their meaning correct definition of law as a social phenomenon. The concept of rights from the standpoint of an integrative approach.